2006
DOI: 10.1080/00480169.2006.36699
|View full text |Cite
|
Sign up to set email alerts
|

Segmental axonopathy of Merino sheep in New Zealand

Abstract: The disorder is the same as that described in Merinos in Australia as segmental axonopathy, and believed to have an inherited aetiology. The lesions and protein changes indicate abnormalities of the cytoskeleton, its relationship with the myelin sheath, and myosin Va molecular motor. The consequence appears to be abnormal axonal transport and inability to maintain the integrity of axons and their myelin sheaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
2
0
2
Order By: Relevance
“…No changes were observed that could give any indication of the origin of the swollen axons. Similar lesions occurred throughout the brain, being particularly severe in the trigeminal nerve radix, inferior cerebellar peduncle and pons as reported in Merinesco sheep (25). They have been reported as frequent incidental findings in sheep, cattle, dogs, pigs, man, and horses with no history of clinical neurologic disease (13).…”
Section: Discussionsupporting
confidence: 57%
“…No changes were observed that could give any indication of the origin of the swollen axons. Similar lesions occurred throughout the brain, being particularly severe in the trigeminal nerve radix, inferior cerebellar peduncle and pons as reported in Merinesco sheep (25). They have been reported as frequent incidental findings in sheep, cattle, dogs, pigs, man, and horses with no history of clinical neurologic disease (13).…”
Section: Discussionsupporting
confidence: 57%
“…Knuckling of the toes and circling is also evident in most cases. 33 Histopathology of the disease resembles that of TSE, except that segmental axonopathy affects mainly white matter and the TSEs involve grey matter.…”
Section: Segmental Axonopathy (Omia 001492) Occurs In Fine-woolmentioning
confidence: 91%
“…32 Studies strongly implicate a genetic basis, as does the recent occurrence in New Zealand of the same disorder, which was linked to importation of rams of the same bloodlines involved in the Australian disease. 33…”
Section: Australian Merinomentioning
confidence: 99%
“…Στην εκτροφή, μπορεί αρχι-κά να εκδηλωθούν κρούσματα αποβολής σε προβατί-νες ή αίγες, οι οποίες προσβλήθηκαν από τον ιό. Εάν το(α) έμβρυο(α) των προσβεβλημένων ζώων επιζή-πλασία/απλασία της παρεγκεφαλίδας, η δυσμορφία Dandy-Walker, η νόσος του τρελού αρνιού (daft lamb disease), η αβιοτροφία της παρεγκεφαλίδας και η β-μαννοσίδωση (Dennis 1993, Pritchard et al 1994, Wessels et al 2003, Johnstone et al 2005, Jolly et al 2006, Esfandiari and Dehghan 2010, Windsor et al 2011.…”
Section: νόσος Border (συγγενής χορεία)unclassified
“…Τα νοσήματα αυτά συνήθως εκδηλώνονται σποραδικά στις εκτροφές (Oruc 2009), σχετιζόμενα με συγκεκριμένους γεννή-τορες, οι οποίοι πρέπει να απομακρυνθούν από την εκτροφή. Μεταξύ αυτών των νοσημάτων περιλαμβά-νονται η νευροαξονική δυστροφία στις φυλές Suffolk και Merino (Dennis 1993, Jolly et al 2006, η υπο-κταση-δυσκαμψία του τραχήλου (οπισθότονος) ή/ και απώλεια της ακοής (Scott 2010b). Ο θάνατος επέρχεται σε 6 έως 10 ημέρες από την εκδήλωση των συμπτωμάτων.…”
Section: παθολογικές καταστάσεις με γενετικό υπόβαθροunclassified